Fingolimod targeting protein phosphatase 2A differently affects IL‐33 induced IL‐2 and IFN‐γ production in CD8+ lymphocytes. Issue 4 (13th January 2016) - Ottenlinger, Florian; Schwiebs, Anja; Pfarr, Kathrin; Wagner, Annika; Grüner, Sophia; Mayer, Christoph A.; Pfeilschifter, Josef M.; Radeke, Heinfried H.
Abstract : Multiple sclerosis patients are treated with FTY720 whose phosphorylated moiety prevents lymphocyte sequestration. Herein we present that (A) FTY720‐P inhibits IL‐33 induced IL‐2 production in EL4‐ST2 cells and (B) nonphosphorylated FTY720 attenuated IFN‐γ production of IL‐33/IL‐12 stimulated CD8+ via SET/PP2A. These results further extend the therapeutic mechanisms of fingolimod in MS. Abstract : Multiple sclerosis patients are treated with fingolimod (FTY720), a prodrug that acts as an immune modulator. FTY720 is first phosphorylated to FTY720‐P and then internalizes sphingosine‐1‐phosphate receptors, preventing lymphocyte sequestration. IL‐33 is released from necrotic endothelial cells and contributes to MS severity by coactivating T cells. Herein we analyzed the influence of FTY720, FTY720‐P, and S1P on IL‐33 induced formation of IL‐2 and IFN‐γ, by using IL‐33 receptor overexpressing EL4 cells, primary CD8 + T cells, and splenocytes. EL4‐ST2 cells released IL‐2 after IL‐33 stimulation that was inhibited dose‐dependently by FTY720‐P but not FTY720. In this system, S1P increased IL‐2, and accordingly, inhibition of S1P producing sphingosine kinases diminished IL‐2 release. In primary CD8 + T cells and splenocytes IL‐33/IL‐12 stimulation induced IFN‐γ, which was prevented by FTY720 but not FTY720‐P, independently from intracellular phosphorylation. The inhibition of IFN‐γ by nonphosphorylated FTY720 was mediated via the SET/protein phosphatase 2A (PP2A) pathway, since a SET peptide antagonist also prevented IFN‐γ formation and the inhibition of IFN‐γ by FTY720 was reversible by a PP2A inhibitor. While our findings directly improve the understanding of FTY720 therapy in MS, they could also contribute to side effects of FTY720 treatment, like progressive multifocal leukoencephalopathy, caused by an insufficient immune response to a viral infection.